Pengaruh Pengenalan Lapangan Persekolahan (PLP) dan Minat Menjadi Guru Terhadap Kesiapan Menjadi Guru pada Mahasiswa Pendidikan Teknik Elektro Universitas Negeri Surabaya - Binti Eka Nur Zulaikah; Nur Kholis; Meini Sondang Sumbawati (Educational Journal, 2026)
This study analyzes the effect of Field Teaching Practice (PLP) and Interest in Becoming a Teacher on Teaching Readiness among Electrical Engineering Education students at Universitas Negeri Surabaya. The study is motivated by preliminary survey findings showing that many students have not achieved optimal teaching readiness despite participating in the PLP program. A quantitative ex post facto design was employed, drawing on Job Readiness Theory and Interest Theory. The population comprised 120 students of the 2021 and 2022 cohorts, all included through total sampling. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression in SPSS 26. The findings show that PLP and Interest in Becoming a Teacher each have a positive and significant partial effect on Teaching Readiness, and that both variables simultaneously exert a significant effect, jointly explaining a substantial share of the variance in Teaching Readiness. The study concludes that teaching readiness is optimally formed through the combination of practical field experience and strong intrinsic motivation to become a teacher, offering both theoretical contribution to teacher-readiness literature in technical education and practical input for strengthening PLP implementation..